(untitled) (Biological Sciences - PJSIR, 2002)
Groundwater in Karachi is influenced mainly by the evaporation / crystallization process as expressed by the Na/ (Na+Ca) weight concentration ratio. The high coefficient of determined between conductivity and total dissolved ions concentration in meq·1 revealed that major ions affect the conductivity of groundwater. It was also found that groundwa ter quality with respect to cations is not significantly influenced by geology, particularly in the Urban area of the city, where the 90% of the population resides . The relationship between conductivity and bicarbonate concentration shows that supersaturation of groundwater with carbon dioxide is responsible for general depression of pH.